Pengaruh Orientasi Pasar Dan Inovasi Produk Terhadap Keunggulan Bersaing Pada PT. Bitratex Industries - Rachmat Setyawan; Agustinus Wardi; Julitta Dewayani (Universitas 17 Agustus 1945 Semarang, 2022)
Main problem: Differences in the results of the influence of market orientation and product innovation on competitive advantage at PT. Bitratex industries. Objective: to analyze the influence of market orientation and product innovation on competitive advantage. Originality: The influence of market orientation and product innovation on competitive advantage at PT. Bitratex industries. Method: The type of information that will be used in this research is subject information (self report information), namely the type of exploratory information in the form of points of view, conclusions, encounters, or the qualities of a person or group that is the subject of research. Results: There is a significant influence of market orientation and product innovation on competitive advantage at PT. Bitratex industries.